A case of the blues: depression screenings in a community pharmacy. Issue 1 (26th December 2019) - Mazzei, Matthew J.; Galdo, John A.
Abstract : Theoretical basis: This case builds on elements of project management (PM) – specifically project initiation – including the development of a project charter and stakeholder analysis. Research methodology: The case was developed from secondary sources as well as first-hand knowledge of the project by one of the authors. This author was on faculty at a private university in the southeastern USA, teaching numerous courses in the pharmacy curriculum while also serving as the Community Practice Residency Director for community pharmacies around the state. While connecting with these organizations, additional revenue requirements and complementary services were frequent topics of attention, leading to a grant to assist pharmacies in building out such services. Through this grant, the author engaged in consultations with community pharmacies around the state, including the pharmacy highlighted via this case. Pseudonyms have been used for the business, and all individuals associated with it, to maintain anonymity. Secondary sources used for additional research include industry reports and related websites. Case overview/synopsis: Richard has owned and operated a community pharmacy, Our Family Farmacy (OFF), for years. A changing industry climate has forced Richard to diversify the products and services he provides. In addition to the distribution of medicine and front-end sales of consumer goods, Richard is seeking to expand into a larger spectrum of healthcare services. After researching several different types of services, and after dealing with related personal family circumstances, Richard decided that OFF should begin their expansion by offering depression screening services. He turned initiation of the project over to his pharmacy intern, Caitlin. Complexity academic level: This compact case is geared toward undergraduate- and graduate-level students taking courses in general management and, more specifically, PM. This case might also be used by students with a career focus in the healthcare sector, and could of particular interest for students in a pharmacy program. Classroom application should encompass discussions on the project initiation process group, particularly with the processes regarding the project charter deliverable and the identification and assessment of project stakeholders.